Social work and anti-oppressive approach: educational practices and housing interventions with Roma and Sinti in Venice - Claudia Mantovan (Educazione Interculturale)
The contribution, using data from various studies conducted in different periods, reconstructs the twenty-year relationship between the social services of the Municipality of Venice and some Sinti and Harvati Roma families, primarily referring to interventions carried out in the area of housing. The article focuses particularly on the peculiar style of social and educational work present in the services that have dealt with Roma and Sinti over the years, reconstructing its origins, characteristics, and effects. This reconstruction leads to the argument that the educators employed in this and in other low-threshold services of the lagoon municipality adopt a modus operandi in tune with what Scarscelli (2022), based on the theoretical perspective of critical social work, defines as an anti-oppressive approach in social work. The contribution highlights how this relational and educational modality has fostered mutual learning and change in both parties: not only in the Roma and Sinti, who have undergone significant changes in their housing style, but also in the educators, who in their relationship with the former have modified their initial ideas in various circumstances and consequently recalibrated the proposed interventions.